2011
DOI: 10.1080/09593330.2011.571713
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the exothermal VOC adsorption in a fixed-bed activated carbon adsorber

Abstract: Activated carbon fixed beds are classically used to remove volatile organic compounds (VOCs) present in gaseous emissions. In such use, an increase of local temperature due to exothermal adsorption has been reported; some accidental fires in the carbon bed due to the removal of high concentrations of ketones have been published. In this work, removal of VOCs was performed in a laboratory-scale pilot unit. In order to visualize the increase in local temperature, the adsorption front was tracked with a flame ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…The choice of these materials rather than activated carbon is mainly due to the exothermic phenomenon associated with values of VOC adsorption enthalpy, usually ranging between 40 and 90 kJ.mol −1 [4,14]. This can yield to high temperature increases depending on levels of treated VOC concentration and may induce significant local warming to start combustion of either the adsorbate or the adsorbent itself, particularly if activated carbon is used [15,16]. Thus additional consideration of safety conditions is required for appropriate engineering and safe operating of adsorption facilities, which in turn needs accurate knowledge of the evolved heat effect values.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of these materials rather than activated carbon is mainly due to the exothermic phenomenon associated with values of VOC adsorption enthalpy, usually ranging between 40 and 90 kJ.mol −1 [4,14]. This can yield to high temperature increases depending on levels of treated VOC concentration and may induce significant local warming to start combustion of either the adsorbate or the adsorbent itself, particularly if activated carbon is used [15,16]. Thus additional consideration of safety conditions is required for appropriate engineering and safe operating of adsorption facilities, which in turn needs accurate knowledge of the evolved heat effect values.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, infrared thermography was used 36 and confirmed that the temperature at the filter center was representative of all temperatures, as illustrated in Figure 4. In fact, when the temperatures were plotted along the horizontal and vertical lines, deviations below 10% were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The applications of such a study are as follows: Processes involving fluid–solid interactions with applications for water and air treatments . In other words, adsorption–desorption processes are implemented, studied, and optimized in the case of complex media. Technological diffusion on applications such as the treatment of volatile organic compounds present in the air and the purification of organic or metallic micropollutions in the water. …”
Section: Introductionmentioning
confidence: 99%
“…• Technological diffusion on applications such as the treatment of volatile organic compounds present in the air and the purification of organic 6 or metallic micropollutions in the water.…”
Section: Introductionmentioning
confidence: 99%